Effectiveness of early generation selection in cowpea for grain yield and agronomic characteristics in semiarid West Africa - Padi, Francis K; Ehlers, J.D. (Wiley, 2008)
The effectiveness of early generation selection for grain yield in a cowpea [Vigna unguiculata (L.) Walp.] population was examined in the Guinea and Sudan savanna agroecologies of Ghana where genotype × location interaction is known to be large. A set of 131 F3:4 lines were developed from a cross between a local cultivar and an unadapted source of large grain size. Mild selection was practiced during line development at one location in the Guinea savanna zone to eliminate poorly adapted lines. Unreplicated F3 plant data were collected on all the lines at the one location during the development of the lines. Multilocation trials were conducted with lines formed by bulk harvest of F4 families to assess how effectively the early generation selection protocol was able to generate superior lines for the target agroecology. Genotypic correlation for grain yield between locations was high only between the two locations in the Guinea savanna zone. Narrow‐sense heritability estimates were low and not different from zero for grain yield, but heritability estimates for days to flowering and seed size were large. F4 lines derived from the highest 10% performing F3 individuals were no higher yielding than F4 lines derived from the remaining F3 individuals, indicating that early generation selection for yield was ineffective. Single‐seed descent (SSD) or bulk breeding methods will be more efficient than pedigree breeding for developing cowpea varieties with high yield potential for this agroecology.